Mobile health services and the elderly: Assessing the determinants of technology adoption readiness in Pakistan. Issue 4 (13th April 2021) - Khan, Tajdar; Khan, Khush Dil; Azhar, Muhammad Salman; Shah, Syed Nadir Ali; Uddin, Mohammed Mahin; Khan, Tariq Habib
Abstract : Technological innovations changed people's daily lives. Wireless technologies, such as mobile phones and other portable gadgets, are becoming an essential part of each generation. With the increasing size of the elderly population around the world, opportunities for the older generation to use wireless technologies, such as gerontechnologies, are increasing. Older adults can use mobile health (mHealth) to receive healthcare at their doorstep. This study uses the UTAUT theoretical framework, extended to perceived ubiquity (PU), perceived trust (PT), and technology anxiety (TA), to investigate the elderly's intention to adopt mobile phone technology for healthcare (i.e., mHealth) in the socioeconomic environment of Pakistan. This study surveys 286 respondents from Islamabad, Pakistan. Structural equation modeling (SPSS version 25 and AMOS version 24) is used to analyze the data. Outcomes show that performance expectancy (PE), effort expectancy, social influence (SI), facilitating conditions, PU, and PT have a positive significant relationship with mHealth adoption intention (AI). However, the results do not indicate the negative relation of TA with mHealth AI. Moreover, gender significantly moderates the relationship between PE and SI and mHealth AI. This study contributes comprehensive knowledge to the existing literature on gerontechnology adoption in the socioeconomic context of a developing economy.